The Influence Of Puskesmas Management On The Quality Of Service Of The Lubuk Batang Sub-District Health Center In Oku District - Agunawan, Agunawan; Munajat, Munajat; E. Yunita (Cita konsultindo, 2025)
Puskesmas is the spearhead of public health services and has a function as the first contact for people in obtaining health services. Until now, the quality of services at puskesmas is still often complained about by the community. Services at puskesmas are also still understood as technical problems of treatment where the services only involve doctors, nurses and other health workers. This research will be conducted at the Lubuk Batang Health Center, OKU Regency. Determination of the location is carried out intentionally (Purposive) with the consideration that it does not have 9 types of complete health workers. the number of existing populations that are used as samples / respondents based on criteria is 50 Respondents of all ASN employees of health workers at Puskesmas Lubuk Batang OKU Regency. The results showed that from several dependent variables HR problems at Puskesmas Lubuk Batang that can affect the quality of service are: The lack of integration of the planning system and procedures for the distribution of health workers; lack of capacity of the HR planning unit at all levels in the distribution of health workers; lack of good communication so that there are differences in understanding, information and knowledge about the distribution of health workers between the planning unit and health service providers; lack of support from the local government; and planning that is not integrated at various administrative levels in the local government of OKU Regency.